GREEN CHEMISTRY SOLVENT-FREE REDUCTIVE AMINATION REACTION OF BENZALDEHYDE AND BENZYLAMINE - NGONGO NARU (NIM: 90514012) , BERNARDUS
Chemical reactions in the laboratory and the chemical industry should be the most economical manner and minimize environmental impact. Chemical reactions must consider aspects of green chemistry. One example of green chemistry into chemical lab is the use of environmentally friendly solvents or free solvent reactions. Reductive amination reaction is one of the chemical reactions that are often studied. This reaction is important because it is known that 20% of the precursor drug molecule synthesized through this reaction. This reaction can be done by applying some aspects of green chemistry. This study aims to carry out the reaction without solvent reductive amination of benzaldehyde and benzylamine. Benzylamine used as a reactant was synthesized by the reaction of ammonia with benzylchloride. Benzylamine product produced with the yield of 54.68%. Benzylamine was then characterized using infrared spectrophotometer, 1H NMR and 13C NMR. Benzylamine infrared spectra, shows two signals at wave number 3423.66 and 3338.78 cm-1. The wave numbers indicate the presence of symmetric and asymmetric stretching vibration which is the hallmark of the aliphatic primary amine. The signal for the C-N bending and N-H wagging which make a total contrast to signals on precursor benzylchloride. Benzylamine 1H NMR spectrum showed three signals, with chemical shift 1.70 ppm, 3.87 ppm and 7.33 ppm indicated the presence of -NH2, -CH2- and benzene groups. Benzylamine 13C NMR spectroscopy showed three signals on chemical shift 53.26 ppm, 128.30 and 140.43 ppm are an aliphatic carbon atoms, benzene, and quaternary carbon atoms, respectively. In the reductive amination reaction also produced dibenzylamine which is a secondary amine. In this study was produced dibenzylamine to yield 24.06% based on the benzylamine mass. IR spectra of dibenzylamine show one signal at wave number is 3313.71 cm-1 in favor of the formation of secondary amines. The 1H NMR spectrum showed the presence of three proton signal 2.05 ppm, 3.83 ppm and 7.28 ppm, superscript related with proton signals of -NH-, -CH2-, and benzene, respectively. Dibenzylamine 13C NMR spectroscopy showed three signals on chemical shift 53.26 ppm ppm 140.40 and 128.30 ppm respectively aliphatic carbon atoms, benzene, and quaternary. IR and NMR spectrum as a whole show was the formation dibenzylamine.